2014
DOI: 10.1080/13546805.2014.973487
|View full text |Cite
|
Sign up to set email alerts
|

Associations between intrusive thoughts, reality discrimination and hallucination-proneness in healthy young adults

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Descriptive statistics for self-report measures and performance on the two tasks, as well as correlations between these variables, are presented in Table 1. Participants made few false alarms on the visual reality discrimination task and detected faces on around half of the trials were a face was presented, which is consistent with non-clinical participants' performance on an auditory reality discrimination task (Smailes, Meins, & Fernyhough, 2015). Participants performed well on the face pareidolia task, detecting a face pareidolia on around 75% of the trials where one was present.…”
Section: Descriptive Statistics and Correlational Analysessupporting
confidence: 75%
“…Descriptive statistics for self-report measures and performance on the two tasks, as well as correlations between these variables, are presented in Table 1. Participants made few false alarms on the visual reality discrimination task and detected faces on around half of the trials were a face was presented, which is consistent with non-clinical participants' performance on an auditory reality discrimination task (Smailes, Meins, & Fernyhough, 2015). Participants performed well on the face pareidolia task, detecting a face pareidolia on around 75% of the trials where one was present.…”
Section: Descriptive Statistics and Correlational Analysessupporting
confidence: 75%
“…It can also account for experimental evidence of an increase in intrusive cognitions in people with AVH and TI, both in the presence (Brebion et al 2010; Brebion et al 2012; see also Marzillier and Steel 2007) and the absence of a specific task (Lobban et al 2002; Morrison and Baker 2000). For example, both healthy individuals prone to hearing voices and patients with ‘thought interference’ (e.g., thought insertion) have higher scores on self-report measures of intrusive thoughts in daily life (e.g., There are thoughts that keep jumping into my head) compared to controls (Linney and Peters 2007; Smailes et al 2015; Varese et al 2010; Vellante et al 2012). …”
Section: An Auditory Processing Stream Frameworkmentioning
confidence: 99%
“…Kelsall-Foreman et al (2020) reported a two-factor model in the general population, one factor being body-centered experiences and the other external experiences. Smailes et al (2015) found that high scorers on CAPS reported more false alarms on an auditory signal detection task, reflecting a tendency to “detect” stimulation when there was none.…”
Section: Methodsmentioning
confidence: 94%